Population structure and genetic diversity of non-native aoudad populations - Sunčica Stipoljev (Nature Portfolio, 2021)
Abstract The aoudad (Ammotragus lervia Pallas 1777) is an ungulate species, native to the mountain ranges of North Africa. In the second half of the twentieth century, it was successfully introduced in some European countries, mainly for hunting purposes, i.e. in Croatia, the Czech Republic, Italy, and Spain. We used neutral genetic markers, the mitochondrial DNA control region sequence and microsatellite loci, to characterize and compare genetic diversity and spatial pattern of genetic structure on different timeframes among all European aoudad populations. Four distinct control region haplotypes found in European aoudad populations indicate that the aoudad has been introduced in Europe from multiple genetic sources, with the population in the Sierra Espuña as the only population in which more than one haplotype was detected. The number of detected microsatellite alleles within all populations (< 3.61) and mean proportion of shared alleles within all analysed populations (< 0.55) indicates relatively low genetic variability, as expected for new populations funded by a small number of individuals. In STRUCTURE results with K = 2–4, Croatian and Czech populations cluster in the same genetic cluster, indicating joined origin. Among three populations from Spain, Almeria population shows as genetically distinct from others in results, while other Spanish populations diverge at K = 4. Maintenance of genetic diversity should be included in the management of populations to sustain their viability, specially for small Czech population with high proportion of shared alleles (0.85) and Croatian population that had the smallest estimated effective population size (Ne = 5.4).